Challenges and opportunities for characterisation of high-temperature polymer electrolyte membrane fuel cells: a review - Zucconi, Adam; Hack, Jennifer; Stocker, Richard; Suter, Theo A. M; Rettie, Alexander J. E; Brett, Dan J. L (Journal of materials chemistry. A, Materials for energy and sustainability, 2024)
High-temperature (120-200 °C) polymer electrolyte membrane fuel cells (HT-PEMFCs) are promising energy conversion devices that offer multiple advantages over the established low-temperature (LT) PEMFC technology, namely: faster reaction kinetics, improved impurity tolerance, simpler water and thermal management, and increased potential to utilise waste heat. Whilst HT- and LT-PEMFCs share several components, important differences in the membrane materials, transport mechanisms and operating conditions provide new challenges and considerations for characterisation. This review focuses on phosphoric acid-doped HT-PEMFCs and provides a detailed discussion of the similarities and differences compared to LT-PEMFCs, as well as state-of-the-art performance and materials. Commonly used characterisation techniques including electrochemical, imaging, and spectroscopic methods are reviewed with a focus on use in HT-PEMFCs, how experimentation or analyses differ from LT-PEMFCs, and new opportunities for research using these techniques. Particular consideration is given to the presence of phosphoric acid and the absence of liquid water. The importance of accelerated stress tests for effective characterisation and durability estimation for HT-PEMFCs is discussed, and existing protocols are comprehensively reviewed focusing on acid loss, catalyst layer degradation, and start-up/shutdown cycling. The lack of standardisation of these testing protocols in HT-PEMFC research is highlighted as is the need to develop such standards. High-temperature polymer electrolyte membrane fuel cells require advancements to capitalise on their advantages over conventional PEMFCs, the critical roles and opportunities for characterisation and durability testing are discussed in this review.